2001
DOI: 10.1117/12.446752
|View full text |Cite
|
Sign up to set email alerts
|

<title>Laser beam shaping via conventional design software</title>

Abstract: Previous efforts have shown that optimization-based techniques, particularly genetic algorithms, can be used to effectively design beam shaping systems for several classes of problems. These techniques have used external programs to perform the optimization, which allow a great deal of optimization flexibility. However, the external program must be understood and tuned for beam shaping applications. For many problems, the flexibility of an external program is not required. This work shows that the internal opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…If the source is assumed to be a point source, then the relationship between angles at the source and positions at the target can be computed using energy balance relationships {e.g., 6,7]. This approach can provide a robust merit function; however, it does not provide a direct measure of the illuminance.…”
Section: Raymentioning
confidence: 99%
“…If the source is assumed to be a point source, then the relationship between angles at the source and positions at the target can be computed using energy balance relationships {e.g., 6,7]. This approach can provide a robust merit function; however, it does not provide a direct measure of the illuminance.…”
Section: Raymentioning
confidence: 99%
“…Keywords: additive technology, selective laser melting, laser modulation, CoCrMo powder DOI: 10.3103/S1068798X15060143 The creation of a spot with a uniform power den sity distribution in the focal plane was considered in [17,18]. By means of inverse Fourier transformations, it was shown that an input beam with an Airy disk dis tribution is required to obtain a uniform power den sity distribution in the focal plane of the lens.…”
Section: Track Geometry In Selective Lasermentioning
confidence: 99%